Acupressure and breast milk production in indonesian postpartum mothers: a scoping review - Prima Kusrini; Jeni Lisu; Regitha Adit Pramesty; Rahma Sasmita Indriani; Lani Gumilang; Qorinah Estiningtyas Sakilah Adnani; Victor Abiola Adepoju (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2026)
Optimal breast milk production is crucial for successful breastfeeding. Acupressure has been used as a non-pharmacological intervention to enhance lactation in postpartum mothers. This scoping review aimed to evaluate the effectiveness of acupressure alone and in combination with other therapies in improving breast milk production and to identify influencing maternal factors. A scoping review was conducted following PRISMA guidelines. Eighteen studies were included from ScienceDirect, Google Scholar, and EBSCO using keywords related to acupressure, breast milk production, and postpartum. Three themes were identified: respondent characteristics modulating lactation; impact of acupressure on lactation; and the efficacy of acupressure combined with other therapies. Acupressure improved breast milk production and adequacy in most studies. Maternal characteristics (age, education, parity, and breastfeeding support) influenced lactation outcomes. Reported effects included increased milk volume, earlier lactation onset, and higher prolactin levels. Acupressure was more effective when combined with interventions such as oxytocin massage, back massage, and aromatherapy. Acupressure is a safe and effective method to enhance breast milk production. Its integration into maternal health services and combination with supportive therapies, tailored to maternal characteristics, may improve breastfeeding outcomes. Future RCTs should use standardized volumetric outcomes, longer follow-up, and compare acupressure combinations with pharmacological interventions.